Success to clear the bar in elite pole vaulters is affected by step frequency perturbation - Theodorou, S. A.; Panoutsakopoulos, V.; Exell, T. A.; Cassirame, J.; Sanchez, H.; Kotzamanidou, M. C. (Journal of Human Kinetics, 2023)
The purpose of the study was to identify the interaction of step characteristics, along with the direction and magnitude of their asymmetry of elite male and female pole vaulters between successful and failed attempts. It was hypothesized that step characteristics and the magnitude of asymmetry between the two legs would interact with the outcome of the attempt. The approach runs of 12 pole vaulters (7 males, 5 females) were recorded during an indoor international competition. The leg used by the athlete for taking-off was defined as the non-pole-carrying leg, while the other was the pole-carrying leg. Using spatiotemporal information obtained from recordings with a panning camera (300 fps), the last steps of each athlete`s approach run were analyzed for length, frequency, average velocity, and inter-limb asymmetry. There was no inter-limb difference (p > 0.05) in the absolute values of step length or step velocity between successful and failed attempts. However, the pole-carrying leg presented significantly (p < 0.05) higher step frequency values at the failed attempts. There was no significant difference (p > 0.05) in asymmetry values for step length, frequency, and average velocity between successful and failed attempts. Although step velocity remained unaffected, failed attempts were characterized by a perturbation in the interaction of step frequency and step length. The present findings suggest that although high velocity at the final phase of the approach is essential, it is not the sole determining factor for a successful attempt.